Portable fresh coconut milk extractor for small and medium industries (SMI) / Ahmad Syahmi Yusneta, Ab Aziz Mohd Yusof and Kamariah Md Isa - Yusneta, Ahmad Syahmi; Mohd Yusof, Ab Aziz; Md Isa, Kamariah (School of Mechanical Engineering, 2023)
A coconut milk extractor is a machine that extracts coconut milk from fresh coconuts. In today's world, it's becoming a viable alternative to the traditional extraction process. The project aims to design and fabricate a portable coconut milk-extracting machine. The machine's advantages are providing more dependable processing time, hygiene, and safety process with fewer processing steps. This product was developed by designing, fabricating, and analyzing a portable coconut milk extractor. Busy urban society, particularly working women, and Small and Medium Industries are the target population and prospective clients (SMI). This machine is developed mainly for Malaysian users since most of the testing is done in this country. The machine can be operated hygienically and requires fast steps. In order to compete in the market, the machine will be sold at a competitive price. The project's goal is to make a smaller and less expensive machine than those already in use in this sector. The machine prototype is built with material availability and fabrication utilities in mind. The prototype's final testing and performance, such as the amount of coconut milk that can be extracted and the prototype's efficiency, are measured. The design is believed to extract a substantial volume of coconut milk while also acting as a user-friendly kitchen gadget, competing with other devices currently on the market